MEKANISME PENDAFTARAN BARU PAJAK BUMI DAN BANGUNAN PADA BADAN PENGELOLAAN KEUANGAN PENDAPATAN DAN ASET DAERAH KOTA BANJARMASIN - Najwah Fabian; Hamdani; Muzdalifah (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
Land and building tax is a derah income that plays a fairly important role in a development. For the new UN-P2 registration process, the BPKPAD office provides a registration form or blank provided at the BPKPAD office. The form is in the form of a new Tax Object Registration Submission sheet, SPOP and or LSPOP PBB-P2 where the sheet must be filled in correctly, clearly, completely and on time. For the Imposition and Determination system of UN-P2 objects used at the BPKPAD office, namely using the Official Assessment System collection system